Thermal analysis of onboard front-end AC/DC converter for EV using advanced semiconductor devices - Kanimozhi Gunasekaran; Ravi Samikannu (Results in Engineering)
Thermal analysis of power converters is essential for predicting temperature distribution, managing heat dissipation, and ensuring the reliability and efficiency of electronic components. Notably, approximately 54 % of all power converter malfunctions are attributed to temperature- related issues. In this research, the study aims to optimize the onboard AC/DC converters installed in EV chargers, since the performance of these converters plays a significant role in achieving high charging speed, long-life batteries, and safety altogether. This paper focuses on the thermal analysis of front-end AC/DC converter in an EV onboard charger. The converter topology chosen is phase shifted boost PFC converter and the performance of the converter is analysed using wide band gap semiconductor devices. The thermal impact on the semiconductor devices under different load and supply conditions is analysed and the results conclude that the efficacy of the converter is obtained as 98 % when the converter utilizes SiC MOSFET/GaN devices which is 1.8 % higher than the Si MOSFET-based converter. This study provides valuable insights into enhancing EV charger efficiency through advanced thermal management techniques.